Kinetic and kinematic changes during a 30-repetition bout of the barbell clean - Swinton, P. A.; Shitanshi, D.; Dolan, E.; Burgess, K.; Singh, B.; Aspe, R. (Journal of Athletic Enhancement, 2016)
The purpose of this investigation was to investigate the biomechanical effects of performing a large number of repetitions with a technically demanding exercise as is recommended in many extreme conditioning programs. Sixteen trained male participants (age: 24.1 ± 4.1 yr; stature: 180.1 ± 3.6 cm; mass: 94.6 ± 10.4kg; resistance training experience: 6.0 ± 3.4 yr) performed 30 repetitions of the barbell clean in as short a duration as possible using the same absolute load of 62 kg. The participants also performed a baseline assessment comprising 6 repetitions with the same absolute load to provide a non-fatigued comparison. Discrete and continuous kinematic variables were quantified using 2D video analysis, whilst kinetics were quantified using force values collected from a force platform. Statistically significant differences in kinematic and kinetic values were observed between the baseline assessment and fatiguing protocol. However, the magnitude of these differences was classified as low to moderate. Knee flexion at the beginning of the movement was significantly lower during the 30 repetition protocol compared with baseline and decreased as fatigue accrued (p<0.001, eta square=0.045). Accumulation of fatigue resulted in decreased hip flexion and increased ankle dorsiflexion at the catch phase (p<0.001,eta square=0.040; p=0.036, eta square=0.044, respectively). In contrast, continuous kinematic variables demonstrated that participants were able to maintain coordinated action between the hip and knee throughout the 30 repetitions. Collectively, the results demonstrate that despite relatively small changes to technique observed at the beginning and end of the barbell clean, the more important coordinative features of the movement can be maintained despite accruing substantial fatigue. It is recommended that if extreme conditioning programs are used with technically demanding resistance exercises then technique should be monitored and the session terminated if improper movement patterns emerge.